Taktir (Garcinia lancifolia Roxb.): A Yester Year Bounty from the Mid Hills of Arunachal Pradesh - Angami, T.; Bhagawati, R.; Makdoh, B.; Nirmal; Assumi, S. R.; Baruah, S. (Indian Forester, 2017)
No Abstract.